2017
DOI: 10.1057/s41305-017-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

The Contemporary Postfeminist Dystopia: Disruptions and Hopeful Gestures in Suzanne Collins’ The Hunger Games

Abstract: Through an analysis of Suzanne Collins’ The Hunger Games trilogy (2008, 2009, 2010), this text will consider the ways in which contemporary postfeminism can be read as a dystopic narrative. The protagonist of the novel (and the rest of the trilogy) is Katniss Everdeen, a young woman who through an ethics of care, disruption of the heteronormative script, and a critical posthuman embodiment offers an alternative to the dystopic present offered by postfeminism. In Katniss’ dystopian world, Collins constructs a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Herein, I analyse how these dystopian games represent their protagonists as undergoing tests, trials and transformations. Familiarity with both texts is assumed here, with a 'spoiler alert' that many plot twists are revealed herein (for a more extensive elaboration, see Kim and Park, 2022;Ruthven, 2017). Within this analysis, both texts are taken as dystopias, although the world of Squid Game only has a shadowy underworld of illicit murderous contests rather than state-level of domination and oppression like The Hunger Games in keeping with classical dystopias.…”
Section: Serious Gamesmentioning
confidence: 91%
See 1 more Smart Citation
“…Herein, I analyse how these dystopian games represent their protagonists as undergoing tests, trials and transformations. Familiarity with both texts is assumed here, with a 'spoiler alert' that many plot twists are revealed herein (for a more extensive elaboration, see Kim and Park, 2022;Ruthven, 2017). Within this analysis, both texts are taken as dystopias, although the world of Squid Game only has a shadowy underworld of illicit murderous contests rather than state-level of domination and oppression like The Hunger Games in keeping with classical dystopias.…”
Section: Serious Gamesmentioning
confidence: 91%
“…Broadly, dystopian games are interpreted by reviewers in mainstream journalism as satires and critiques of capitalism, highlighting how individuals are increasingly pitted against each other in competitions which are deadly for losers and which corrupt winners. (Bouchard, 2022; Ruthven, 2017; Tompkins, 2018). More specifically, The Hunger Games has been read as reflecting the pressures on young people from education to social media (Leigh, 2015), and Squid Game has been taken as a meta-commentary on indebtedness in the economy and dehumanization at work (Abdelmahmoud, 2021; Di Placido, 2021; Wong, 2021).…”
Section: Playing With Theory and Culturementioning
confidence: 99%
“…Una de las críticas más habituales al modelo del monomito es que está pensado para encajar en héroes masculinos (Phillips, 2017). Sin ser este un estudio sobre género en las historias superheroicas adolescentes, no podemos obviar estudios recientes (Raya, 2019) que han incidido en la necesidad de señalar las variaciones, o mejor dicho, las dificultades añadidas a las que se enfrentan las heroínas en relatos de aventuras, específicamente tras el éxito de series protagonizadas por heroínas adolescentes como Buffy Cazavampiros (Early, 2001;Frankel, 2014;Pender, 2018) o películas como Los juegos del hambre (Menéndez y Fernández, 2015;Ruthven, 2017;Golban y Fidan, 2018). Ya hace tiempo que se ha intentado dar una respuesta unificadora a las posibles diferencias entre héroes masculinos y femeninos, principalmente con el desarrollo del concepto de duomito (Pratt, 1981;Pearson y Pope, 1981, Haunert, 1983 por el que se determina que, incluso cuando las etapas y las dificultades que atraviesan hombres y mujeres en su periplo como héroes no sea exactamente igual, la meta y los objetivos (adquirir conocimiento, sobrevivir a la aventura) sí que serían equivalentes.…”
Section: Marco Teóricounclassified
“…It blurs the lines between femininity and masculinity as well as framing both heterosexuality and queerness. Ruthven (2017) observed The Hunger Games focusing on the postfeminist dystrophic issues. She found that Katniss's acts of rebellions in The Hunger Games trigger her impulse to look after others (her district and her family).…”
Section: Introductionmentioning
confidence: 99%